2014
DOI: 10.19030/iber.v14i1.9031
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Commitment In Saudi Arabia And Need For Educational Reforms For The Jobs Of The Future

Abstract: Saudi Arabia is an important country among the Middle Eastern nations and a pivotal one because of its key position in international petroleum production. Sustainable practices are becoming prominent considerations among public and private sector Saudi Arabian business enterprises. Secondary and primary data pertaining to sustainability and carbon management practices in Saudi Arabia and its business enterprises were analyzed in this study. Saudi Arabian government has been serious in tackling the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Alshuwaikhat et al (2016) aimed to assess sustainability practices in higher education institutions in Saudi Arabia through surveying the administrators of these institutions regarding the extent to which the concept of sustainability is integrated into teaching, research and scholarships, campus operations, community service and financial management. Hashmi et al (2015) aimed to analyze sustainability practices, especially in carbon management in Saudi Arabia, by comparing managers' willingness and eagerness to deal with carbon management problems in private sector companies and public sector institutions. The second reason, as Heinzelmann (2016) point out, since the accounting education differ between countries, there might also be differences in the extent to which sustainability issues are covered in the educational contexts in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Alshuwaikhat et al (2016) aimed to assess sustainability practices in higher education institutions in Saudi Arabia through surveying the administrators of these institutions regarding the extent to which the concept of sustainability is integrated into teaching, research and scholarships, campus operations, community service and financial management. Hashmi et al (2015) aimed to analyze sustainability practices, especially in carbon management in Saudi Arabia, by comparing managers' willingness and eagerness to deal with carbon management problems in private sector companies and public sector institutions. The second reason, as Heinzelmann (2016) point out, since the accounting education differ between countries, there might also be differences in the extent to which sustainability issues are covered in the educational contexts in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Later, employee behavior, product and market leadership, and public responsibility are included in the list [86]. Firms typically utilize traditional financial ratios to gauge their performance, which is not potent for measuring growth and sustainable performance in the long run [87,88], as many have reported these financial ratios as short-term [89,90]. These financial ratios may need to spot the bigger picture.…”
Section: Sustainable Firm Performancementioning
confidence: 99%
“…5. Few TBL articles discussed the economic aspect to address sustainability during the initial stage, but a growth trend is observed, as increasingly more large businesses began to consider their sustainability initiatives in association with economic performance more seriously (Hashmi et al 2014). Carter and Rogers (2008) demonstrated that firms that attempt to simultaneously maximize their performance across the three aspects of the TBL will outperform firms that attempt to achieve high levels of social and environmental performance without explicitly considering economic performance.…”
Section: Economic Aspectmentioning
confidence: 99%